41. APLIQUE a propriedade distributiva nas expressões a seguir:
A) (-5).(-6 + 4) =
C) (-2). (1 - 3) =
B) (+3).(-4 - 6) =
D) 7.(-1 + 4) =
E) (-4). (8 - 3) =
F) (-3).(-2 - 7) =
Respostas
respondido por:
6
Explicação passo-a-passo:
A) (-5).(-6 + 4) = (-5)×(+2)=-10
C) (-2). (1 - 3) =(-2)×(+2)=-4
B) (+3).(-4 - 6) =(+3)×(-10)=-30
D) 7.(-1 + 4) =7×3=21
E) (-4). (8 - 3) =(-4)×5=-20
F) (-3).(-2 - 7) =(-3)×(-9)=27
Espero ter ajudado!!!
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás